1997
DOI: 10.1038/bjc.1997.364
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of topotecan in human tumour cell lines and primary cultures of human tumour cells from patients

Abstract: Summary The cytotoxic activity and cross-resistance pattern of the novel topoisomerase inhibitor topotecan (Topo) were investigated in ten cell lines, representing different mechanisms of cytotoxic drug resistance, and in 218 fresh human tumour samples using the fluorometric microculture cytotoxicity assay (FMCA). Resistance to Topo in the cell lines was associated with expression of the multidrug resistanceassociated protein (MRP), whereas the cell lines with P-glycoprotein (P-gp), topoisomerase 11 and glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
(16 reference statements)
0
26
0
Order By: Relevance
“…CPT and its analogue CPT-11/SN38 are very poor substrates for the P170-glycoprotein (P-gp or MDR)-mediated transport and are not affected by the MRP. A reduced uptake of the drug unrelated to P-gp and MRP was found in ovarian cancer cell lines [44]. Independently of known resistance mechanisms, a cross-resistance of topo I inhibitors with mitoxantrone was observed [45].…”
Section: Resistance To Topo I Inhibitorsmentioning
confidence: 91%
“…CPT and its analogue CPT-11/SN38 are very poor substrates for the P170-glycoprotein (P-gp or MDR)-mediated transport and are not affected by the MRP. A reduced uptake of the drug unrelated to P-gp and MRP was found in ovarian cancer cell lines [44]. Independently of known resistance mechanisms, a cross-resistance of topo I inhibitors with mitoxantrone was observed [45].…”
Section: Resistance To Topo I Inhibitorsmentioning
confidence: 91%
“…In addition, data from our laboratory showed that PAK-200S at non-cytotoxic concentrations significantly reversed MRP-mediated 250-fold resistance to doxorubicin in MRP-expressing human fibrosarcoma HT1080/Dr4 cells. Since recent data suggest that MRP may also confer resistance to topotecan in vitro (Jonsson et al, 1997;Jansen et al, 1998) and in vivo (U Vanhoefer et al, unpublished data), PAK-200S may have clinical advantages over other MDR-reversing agents (e.g. PSC-833), lacking significant inhibition of MRP-function (Twentyman et al, 1994;Vanhoefer et al, 1996).…”
Section: Top-i Dna Unwinding Activitymentioning
confidence: 99%
“…Activity was observed in sarcoma and childhood solid tumors demonstrating effectiveness even in cell lines expressing common mechanisms of cytostatic drug resistance such as p-glycoprotein (MDR) and glutathioneassociated resistance [12,13]. In addition, topotecan has also demonstrated activity against osteosarcoma xenografts, in particular when given as an oral formulation [14].…”
Section: Results Of Topotecan In Adult Soft-tissue Sarcomamentioning
confidence: 96%
“…In addition, topotecan has also demonstrated activity against osteosarcoma xenografts, in particular when given as an oral formulation [14]. Inhibition of cell lines derived from childhood sarcomas such as leiomyosarcoma and rhabdomyosarcoma has been demonstrated in vitro and in xenografted nude mouse models [12][13][14]. The Canadian Sarcoma Group has conducted a phase II study of topotecan given at the established schedule of 1.5 mg/m 2 per day for 5 consecutive days every 3 weeks in patients with previously untreated metastatic soft-tissue sarcomas.…”
Section: Results Of Topotecan In Adult Soft-tissue Sarcomamentioning
confidence: 99%